Feedback regulation of ALDOA activates the HIF-1α/MMP9 axis to promote lung cancer progression - Chang, Yu-Chan; Chan, Yung-Chieh; Chang, Wei-Ming; Lin, Yuan-Feng; Yang, Chih-Jen; Su, Chia-Yi; Huang, Ming-Shyan; Wu, Alexander T.H.; Hsiao, Michael (Cancer letters, 2017)
Distant metastasis and recurrence are the greatest challenges in the clinical management of lung cancer. Despite advances in targeted therapies, high mortality rates persist. Therefore, alternative therapeutic interventions are urgently required. Accumulating evidence indicates that normalizing tumor metabolism may be a way to increase therapeutic efficacy and to reduce tumor malignancy. Here, we analyzed integrated transcriptomics data and an shRNA library against glycolytic enzymes and found that elevated Aldolase A expression is highly correlated with metastatic potential and a poor prognosis in patients with non-small cell lung cancer (NSCLC). We validated our in silico findings with an immunohistochemical analysis of clinical samples. Aldolase A silencing significantly suppressed metastatic potential both in vitro and in vivo, whereas the ectopic overexpression of Aldolase A resulted in the opposite phenotype. Furthermore, our microarray and Ingenuity Pathway Analyses (IPA) revealed that Aldolase A-driven lung cancer metastasis was closely linked to hypoxia inducible factor 1 alpha (HIF-1α)-downstream signaling. Importantly, Aldolase A overexpression may promote the release of lactate to block PHD activities and further induce HIF-1α stabilization. Aldolase A and nuclear HIF-1α overexpression levels were positively correlated and were significantly associated with a poorer survival rate in lung cancer patients (P = 0.008 for Overall Survival, P = 0.021 for Disease-free Survival). Furthermore, MMP9, a downstream target of HIF-1α, was significantly upregulated after ALDOA overexpression. A MMP9 inhibitor significantly inhibited cell invasion and migration in ALDOA-HIF-1α axis-induced lung cancer. In summary, our results reveal the molecular mechanism of Aldolase A in promoting lung cancer metastasis via PHD-mediated stabilization of HIF-1α and the subsequent activation of MMP9. The ALDOA-HIF-1α axis may provide a new therapeutic target for metastatic lung cancer treatment. •ALDOA was overexpressed in malignant cells and tumor tissue.•ALDOA-HIF1α axis is prognostic factor and significantly associated with disease recurrence, patient survival rate in clinical.•ALDOA overexpression enhances HIF-1α protein stability by inhibiting HIF-1α hydroxylation.•Therapeutic effect through modulation of ALDOA/Lactate/HIF-1α axis activates MMP9 in lung cancer metastasis.